(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Corrosion remains a persistent challenge in the protection of industrial steel structures, particularly in acidic environments. Therefore, the present study focuses on the synthesis and evaluation of two novel Mannich base derivatives (M1 and M2) as efficient corrosion inhibitors for mild steel using both experimental and computational approaches. The derivatives were synthesized via a one-pot reaction involving acetophenone, formaldehyde, and substituted aromatic amines.